Direction of Trade Statistics Quarterly, December 2012. (Direction of Trade Statistics; Direction of Trade Statistics, 2012)
The Direction of Trade Statistics Online service provides data on the value of merchandise exports and imports between each country and all its trading partners. The database includes: total bilateral and multilateral exports and imports aggregated at national or regional group level; data from 1948 at monthly, quarterly, and annual frequencies.